- #1

fableblue

- 17

- 0

So, could someone explain why when using the parallelogram rule for obtaining the sum of 2 forces by the means of the Law of Cosines that the controller

**-2bc**is replaced by

**+2bc**in the equation a

^{2}=b

^{2}+c

^{2}-2bccosA

example:

The magnitude of two forces exerted on a pylon are FAB=100 and FAC=60 with angle BAC=30degrees

[tex]\Sigma[/tex]FAB+FAC=[tex]\sqrt{}[/tex](60

^{2}+100

^{2}-2(600*100)cos30) = 56.637 FALSE

[tex]\Sigma[/tex]FAB+FAC=[tex]\sqrt{}[/tex](60

^{2}+100

^{2}+2(600*100)cos30) = 154.895 TRUE